2018
DOI: 10.1108/vjikms-10-2017-0069
|View full text |Cite
|
Sign up to set email alerts
|

Inter-organizational knowledge transfer in Omani SMEs: influencing factors

Abstract: Purpose Inter-organizational knowledge transfer (IOKT) is important especially for small and medium enterprises (SMEs). Organizations need external knowledge to improve learning capabilities and their own competitiveness. SMEs are important for every nation’s economy. IOKT can enable SMEs’ learning and innovation and consequently its contribution to the national economy. This study aims to examine the factors that influence the IOKT process in Omani SMEs. Design/methodology/approach This study uses qualitati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 40 publications
0
9
0
Order By: Relevance
“…Taking advantage of this rationale, Roxas and Chadee’s ( 2016 ) study reveals that KM orientation—the extent to which a firm can search, acquire, assimilate, and integrate external knowledge—is an important factor in improving relational capital and thereby increasing innovation capability. Al-Jabri and Al-Busaidi ( 2018 ) have shown that knowledge transfer from outside the organisation (in their study from other organisations) enhances internal learning capabilities because when external knowledge is acquired it is often new and unknown to employees which gives room to the development of new competencies as part of the learning process. Taghizadeh et al ( 2021a ) stressed how essential it is for small firms to possess capabilities to gain access to knowledge beyond the boundaries of the organisation.…”
Section: Presentation Of Findingsmentioning
confidence: 99%
“…Taking advantage of this rationale, Roxas and Chadee’s ( 2016 ) study reveals that KM orientation—the extent to which a firm can search, acquire, assimilate, and integrate external knowledge—is an important factor in improving relational capital and thereby increasing innovation capability. Al-Jabri and Al-Busaidi ( 2018 ) have shown that knowledge transfer from outside the organisation (in their study from other organisations) enhances internal learning capabilities because when external knowledge is acquired it is often new and unknown to employees which gives room to the development of new competencies as part of the learning process. Taghizadeh et al ( 2021a ) stressed how essential it is for small firms to possess capabilities to gain access to knowledge beyond the boundaries of the organisation.…”
Section: Presentation Of Findingsmentioning
confidence: 99%
“…eCommerce, for instance, empowers organizations to enter the global market and, therefore, increase their revenue. ICT has positive performance impacts on small and medium-sized enterprises (SMEs) in Oman (Ashrafi and Murtaza, 2008;Al-Jabri and Al-Busaidi, 2018). SMEs and start-up firms are critical for the KE (Paoloni et al, 2019).…”
Section: Information and Communications Technology For The Development Of The Economics Pillarmentioning
confidence: 99%
“…Since tacit knowledge is personal and un-codified knowledge, therefore, a formal communication of it is difficult as opposed to explicit knowledge which can easily be transferred via formal channels and in a systematic language (Nonaka, 1994;Ellis & Roever, 2018;Hadjimichael & Tsoukas, 2019). Organizational knowledge transfer is heavily dependent on the clarity of knowledge sources and their subsequent transmission, interpretation, and absorption (Hansen, 1999;Kogut & Zander, 1992;Al-Jabri & Al-Busaidi, 2018). The value of knowledge for the knowledge holder plays an important role in the ToK process.…”
Section: B Necessary Conditions For Knowledge/materialmentioning
confidence: 99%